Development of regression equation for heat capacity and density of nanofluids properties - Mohd Taufiq, Awang @ Mohammed (2010)
This research focused on the development of regression equation for nanofluids properties. Nanofluid is the mixing fluid with the nanoparticles size material with effective properties to increase the heat transfer process in such cooling system. This is because base fluid such as water and ethylene glycol that is widely used has poor properties. Beside changes the active factors such as fin or temperature different, nanofluids being develop as a passive factor to increase the heat transfer process. Therefore, it can reduce the space of system. The main idea in this pioneered to increase the heat transfer process but before that the properties should be determined first. Moreover, there is no correlation or standardized value for nanofluid properties since it is new technology, developments of regression equation for nanofluid properties were being conducted. In this study, the properties of nanofluids just focus on specific heat and density. The analysis were using nanoparticles that always been used in industries and also that sited by previous researchers, there are alumina (Al2O), titanium dioxide (TiO2), copper oxide (CuO), silica (SiO2), zirconium dioxide (ZrO23), zinc oxide (ZnO), and silicon carbide (SiC). Development of equations is using FORTRAN with the input data were generated from standard mixture equations. The equation was developed with linear regression with a function of bulk temperature (5C - 70C) and volume concentration (0% - 4%) of water-based nanofluids. Four linear equations have been developed; there are specific heat of nanofluids, specific heat ratio of nanofluids, density of nanofluids, and density ratio of nanofluids with average deviation of 2.22%, 2.22%, 2.25% and 2.24%, respectively. The equations were verified with various authors in the literatures and showed a good agreement with average deviation less than 3%.